Optimal interlesion distance in ablation index-guided pulmonary vein isolation for atrial fibrillation - Kobayashi, Shuhei; Fukaya, Hidehira; Oikawa, Jun; Saito, Daiki; Sato, Tetsuro; Matsuura, Gen; Arakawa, Yuki; Shirakawa, Yuki; Nishinarita, Ryo; Horiguchi, Ai; Ishizue, Naruya; Kishihara, Jun; et al. (Journal of Interventional Cardiac Electrophysiology, 2021)
Purpose Ablation index (AI) is a useful tool of the CARTO® system to make effective lesions during pulmonary vein isolation (PVI) for atrial fibrillation (AF). However, the optimal distance between neighboring ablation points (interlesion distance (ILD)) is still unclear. Here, we evaluated the optimal ILDs in the AI-guided PVI. Methods Forty-nine AF patients who underwent AI-guided PVI in our institute from July 2018 to March 2019 were retrospectively enrolled in this study. Target AI was set at 500 and 400 for anterior and posterior walls, respectively, and we compared the ILDs with and without electrical gaps after a first encircling PVI. Results In both PV, the ILDs with electrical gaps were longer than those without electrical gaps. The best cutoff values of ILD to detect the electrical gaps using the ROC curve were 5.4 mm for the RPV anterior wall (AUC, 0.67; sensitivity, 0.42; specificity, 0.84, P < 0.01) and 4.4 mm for the RPV posterior wall (AUC, 0.68; sensitivity, 0.91; specificity, 0.39, P < 0.01). Similarly, the best cutoff values of ILD were 5.5 mm for the LPV anterior wall (AUC, 0.74; sensitivity, 0.65; specificity, 0.82, P < 0.01) and 5.1 mm for the LPV posterior wall (AUC, 0.67; sensitivity, 0.79; specificity, 0.53, P =0.03). Conclusion The optimal interlesion distances for PVI were different in each PV segment. To achieve the first-pass isolation, less than 5.4/4.4 mm for the RPV anterior/posterior and 5.5/5.1 mm for the LPV anterior/posterior walls of interlesion distances were the best cutoff values in the patients with AF.